Analyzing Communication in and Around Organizations: A Critical Hermeneutic Approach - Phillips, Nelson; Brown, John L. (Academy of Management Journal, 1993)
One of the most interesting potential contributions of culture research lies at the intersection of the study of culture and the study of power. At this intersection lies a process of communication in which interested actors present particular understandings of the world in the hope of creating or sustaining preferred patterns of social relations. In this process, groups and individuals struggle to create and disseminate cultural forms that support preferred patterns of power and dominance. This article presents a methodology, critical hermeneutics, useful in analyzing these attempts. To underscore the usefulness of the approach, we applied the method to a corporation's image advertising campaign, a set of texts intended to restructure the corporation's image and reframe a set of issues in a way favorable to it.